When narration over helmed poetry - Ahmad, Rokia A. (Al-Adab Journal, 2019)
Then comes narration , a storytelling characteristic , into the poem as a raw material as we can see in the Intimate diary which is a combination of the narration of the later and the previous and the later and that is when the narrator stops narrating in the past tense from time to time with the aim of metaphorical commentary in the present tense, in other words, alternately recalling the facts with the comment on them, "1, especially as he enters the texture of the poem from the wider door, and gives the indication that gives the opportunity to resurrect more and in a more easy manner, in the course of it turns out that the narration has the ability to disclose first without paying attention to what has passed, and secondly , it releases the imagination process to its utmost limits , this is evident with the free poem and the prose poem, as it partially abandoned its musical and formative limitations.